Relationship between pregnant women’s internet use and their thoughts about self and baby’s health - Polat, Filiz; Karasu, Fatma (Journal of Dependence, 2022)
Objective: This research was carried out with the aim of examining the relationship between internet use in pregnant women and their thoughts about the health of their baby. Method: The descriptive cross-sectional study was conducted with 216 pregnant women registered in two Family Health Centers between November 2021 and February 2022. The data of the study were collected using the Personal Information Form, the Prenatal Decision-Making Scale for Pregnants, and the Prenatal Self-Assessment Scale’s Thoughts About Self and Baby’s Health Sub-dimension. Results: A statistically significant difference was found between the abortion/abortion history, number of pregnancies and current pregnancy desire status of the pregnant women and the total mean score of the Internet Decision Making Scale for Pregnants. A statistically significant difference was determined between the current pregnancy-related risk/disease status of pregnant women and the means cores of the Opinions About Self and Baby’s Health Sub-Dimension. It was determined that the mean score of the Pregnant Women’s Decision-Making Scale on the Internet was 34.75±7.13 and the Sub-dimension of Thoughts About Self and Baby’s Health was 23.71±5.16. A positive correlation was found between the total and sub-dimensions of the Pregnant Women’s Internet Decision-Making Scale and the Opinions About Self and Baby’s Health Sub-dimension. Conclusion: As the decision-making level of pregnant women increases via the internet, their thoughts about improving their own health and the health of their baby also increase.